THE RELATIONSHIP BETWEEN POCKET MONEY AMOUNT AND BREAKFAST HABITS WITH CHILDERN’S NUTRITIONAL STATUS AT SDN 1 MULYASARI - Widiansyah, Raka Unggul; Elvandari, Milliyantri; Sefrina, Linda Riski (HEARTY, 2025)
The nutritional status of elementary school children is influenced by various factors, including breakfast habits and the amount of pocket money received each day. This study aims to determine the effect of pocket money and breakfast habits on the nutritional status of children at SDN 1 Mulyasari. This study employs a quantitative approach with a cross-sectional design. The sample consists of 48 students selected through total sampling. Data were collected via questionnaires and anthropometric measurements using the body mass index (BMI) according to age. Data analysis was conducted using univariate and bivariate methods (chi-square test with Fisher’s exact test as an alternative). The results show that most respondents have high pocket money (91.7%) and often eat breakfast (72.9%). The majority of respondents (72.9%) have a normal BMI. There was no significant relationship between pocket money and BMI (p = 0.445), nor between breakfast frequency and BMI (p = 0.254). The conclusion of this study is that the amount of pocket money and breakfast habits do not have a strong influence on children’s nutritional status. These findings are expected to serve as a consideration for schools and parents in fostering healthy eating habits in children.